BET 2: Ability of a normal gait examination to rule out cerebellar stroke in acute vertigo. Issue 11 (18th October 2018) - Greer, Alisha; Hewitt, Mark
Abstract : A short-cut review was carried out to establish whether a normal gait examination can rule out cerebellar stroke in patients with acute vertigo. 16 studies were relevant to the question. The author, year and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. The clinical bottom line is that a normal gait examination cannot rule out a cerebellar stroke but the presence of an abnormal gait can be associated.